AN ANALYSIS OF RHETORICAL MOVE AND TRANSLATION TECHNIQUES IN UNDERGRADUATE THESIS ABSTRACTS WRITTEN IN TWO LANGUAGES - Zalinda Salsabilla Firdausyiah; Budi Hermawan; Dian Dia-an Muniroh (JOALL (Journal of Applied Linguistics and Literature), 2021)
An abstract is a brief overview of a research paper. Indonesian undergraduate students are often required to submit their thesis abstracts in Indonesian and English. Various studies related to rhetorical move and translation techniques of abstracts have been done previously, but not many analyzed undergraduate students’ thesis abstracts across languages. Therefore, this study aims to analyze the move-step of the abstracts, and to see translation techniques in different abstract moves. This study used 60 undergraduate thesis abstracts from English Language and Literature and Indonesian Language Literature study programs as the data. As the framework for the data analysis, this study employed Hyland’s (2000) five-move model and Molina & Albir’s (2002) translation techniques. The findings show that despite writing in different languages, both Indonesian and English abstracts were realized with similar rhetorical moves and steps. Move 3 and 4 were found in all of the abstracts, while Move 5 was only realized in small numbers across languages. In relation to translation techniques, it is found that Literal translation is used more frequently than other translation techniques. This study recommends a more extensive study that involves more data from different fields to expand the existing knowledge relating to rhetorical move and translation techniques in the academic field, especially in undergraduate students’ abstracts.